Effect of therapeutic and prophylactic complex DLK (Dironet, Lactobifadol, Forage Keratin) on the intestinal microbiocenosis of the Blue Frost fox at toxascariosis - A. P. Konovalov; I. I. Tsepilova; F. I. Vasilevich; S. Y. Pigina (Российский паразитологический журнал, 2021)
The purpose of the research is determining the effect of the therapeutic and prophylactic complex of Dironet, Lactobifadol and fodder Keratin (DLK) on the qualitative and quantitative composition of the intestinal microflora affected by toxascariosis in the Blue Frost fox.Materials and methods. The research was carried out on the Fur Breeding Farm “Vyatka”, Slobodskoy District, the Kirov Region. The study objects were 24 female Blue Frost foxes culled from the breeding herd. To determine the quality of the skins obtained from the experimental animals, we sorted flint-dried skins.Results and discussion. After the introduction of the therapeutic and preventive complex DLK into the diet of sick animals, the positive dynamics was observed in the quantitative and qualitative composition of intestinal microorganisms. In animals of the experimental groups that were administered DLK, the number of bifidus bacteria, lactic bacteria and fecal enterococci increased; there was a significant decrease or complete absence of pathogenic and conditionally pathogenic microorganisms, fusobacteria, streptococci, clostridia, typical lactose-negative and hemolytic Escherichia, aureus and saprophytic staphylococcus, common Proteus and fungi of the Candida genus. In animals infected by Toxascaris leonina that did not receive the complex therapy, a decrease in lactic acid bacteria and an increase in the content of pathogenic and commensal microorganisms were noted. Under the output of the fur production, the infected animals showed the lowest percentage of skins in terms of quality of 7.16%, which was 0.38% less in comparison with healthy foxes, and 0.51% less in comparison with treated Blue Frost foxes.